2018
DOI: 10.21873/cgp.20102
|View full text |Cite
|
Sign up to set email alerts
|

MGMT Gene Promoter Methylation Status – Assessment of Two Pyrosequencing Kits and Three Methylation-specific PCR Methods for their Predictive Capacity in Glioblastomas

Abstract: Background: Although methylation of the O 6-methylguanine-DNA methyltransferase (MGMT) gene promoter predicts response to temozolomide in patients with glioblastoma, no consensus exists as to which assay is best for its detection. Materials and Methods: Methylation of MGMT promoter was examined by methylation-specific polymerase chain reaction (MSP), quantitative real-time MSP, methylation-sensitive high-resolution melting analysis, and two commercial pyrosequencing (PSQ) kits. Survival was compared among 48 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 42 publications
0
40
0
Order By: Relevance
“…Clinical performance of the "targeted methylation assay" was evaluated in another CCGA nested study that included 2301 participants (1422 cancer [> 20 tumor types, all stages], 879 noncancer). The sensitivity of the assay across all cancer types ranged from 59 to 86% (at 99% specificity), with 34% (95% CI 27-43) sensitivity in stage I (n = 151), 77% (95% CI 70-83) in stage II (n = 171), 84% (95% CI [79][80][81][82][83][84][85][86][87][88][89] in stage III (n = 204), and 92% (95% CI 88-95) in stage IV (n = 281). Moreover, the assay assigned tissue of origin to 94% of cancers in the study and for 90% of these cases, the assignment of TOO was correct [70].…”
Section: Early Detection Of Cancer Regardless Of Its Typementioning
confidence: 99%
See 1 more Smart Citation
“…Clinical performance of the "targeted methylation assay" was evaluated in another CCGA nested study that included 2301 participants (1422 cancer [> 20 tumor types, all stages], 879 noncancer). The sensitivity of the assay across all cancer types ranged from 59 to 86% (at 99% specificity), with 34% (95% CI 27-43) sensitivity in stage I (n = 151), 77% (95% CI 70-83) in stage II (n = 171), 84% (95% CI [79][80][81][82][83][84][85][86][87][88][89] in stage III (n = 204), and 92% (95% CI 88-95) in stage IV (n = 281). Moreover, the assay assigned tissue of origin to 94% of cancers in the study and for 90% of these cases, the assignment of TOO was correct [70].…”
Section: Early Detection Of Cancer Regardless Of Its Typementioning
confidence: 99%
“…The performance of that test was evaluated in a study that included 48 primary GBM samples, using four meningioma samples as negative controls. The study showed that the therascreen® MGMT Pyro® Kit, accurately detects MGMT promoter methylation and can be used for patients stratification according to OS (hazard ratio (HR) of 2.3348 (95% CI 1.1918-4.5724; p = 0.013) [82].…”
Section: Glioblastomamentioning
confidence: 99%
“…2c and 4b). However, some patients who are below this arbitrary cutoff value (e.g., 10%) do respond to TMZ therapy [31][32][33], placing them in a "gray zone" and producing a clinical quandary. With this in mind, Chai et al developed a novel CpG averaging model for pyrosequencing data that defines the MGMT promoter as being methylated when at least 3 CpGs exceed their respective cutoff values; this allows clinicians to better stratify patients with very low levels of methylation (e.g., < 10%) [34].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified two regions (the promoter and gene body) that are significantly correlated with MGMT expression [ 11 ]. However, due to the difficulty of designing a primer for the GC-rich promoter area and the lack of a method that enables analysis of long PCR products at low cost, the region of the gene body is generally selected as the target for MGMT methylation analysis [ 12 ]. To demonstrate the effectiveness of methylation analysis in the promoter region, a new method for analyzing longer PCR products is required.…”
Section: Introductionmentioning
confidence: 99%